Product presentation in the live-streaming context: The effect of consumer perceived product value and time pressure on consumer’s purchase intention - Zhang, Nan (Frontiers in Psychology, 2023)
Live-streaming is conducive to consumers obtaining rich and accurate product information, by displaying products through real-time video technology. Live-streaming provides a new type of product presentation method, such as showing products from different perspectives, interacting with consumers by trying the products out, and answering consumer’s questions in real-time. Other from the current research focus on anchors (or influencers) and consumers in live-streaming marketing, this paper tried to explore the way of the product presentation and its effect and mechanism on consumer’s purchase intention. Three studies were conducted. Study 1 (N=198, 38.4% male) used a survey to explore the main effect of product presentation on consumer’s purchase intention and mediating effect of the perceived product value. Study 2 (N=60, 48.3% male) was a survey-based behavioral experiment and tested the above effects in the scenario of food consumption. Study 3 (N=118, 44.1% male) tried to deeply discussed the above relationship in the appeal consumption scenario by priming different levels of product presentation and time pressure. The results found that the product presentation positively affected consumer’s purchase intention. The perceived product value played a mediating role in the relationship between product presentation and purchase intention. Besides, different levels of time pressure in the living room moderated the above mediation effect. When time pressure is high, the positive impact of product presentation on purchase intention is strengthened. This article enriched the theoretical research on product presentation by exploring product presentation in the context of live-streaming marketing. It explained how product presentation could improve consumer’s perceived product value and the boundary effect of time pressure on consumer’s purchase intention. In practice, this research guided brands and anchors on designing product display to improve consumer’s purchase decisions.